Adverse drug reactions in the elderly of Matanzas, Cuba 2014-2019 - Santos Muñoz, Leidy; Garcia-Milian, Ana Julia; Linares Morera, Anmy; Vidal Casal, Joan Javier (Horizonte Sanitario, 2022)
Objective: To characterize suspected adverse drug reactions that occurred in older adults in Matanzas, from 2014 to 2019. Materials and methods: Pharmacovigilance (FV) case series study. The database of reports of suspected adverse drug reactions of the Provincial Pharmacovigilance Coordinating Unit, between 2014 and 2019, was reviewed. Results: A total of 1926 reports of adverse drug reactions in the elderly were evaluated, representing 24, 3% of the total. Women (56.7%) and the age group between 60 and 69 years (51.4%) predominated. Skin rash prevailed (13.4%). Antimicrobials and non-steroidal anti-inflammatory drugs were the ones most associated with ADRs in the skin, as well as in the digestive system. Cough was related to captopril. Adverse drug reactions of low frequency (55.2%), moderate (83.8%) and probable (77.1%) prevailed according to immutability. Conclusions: The safety profile in the elderly in the province of Matanzas shows a predominance of frequent, moderate and probable adverse reactions in women aged between 60 and 69 years. Antimicrobials, angiotensin-converting enzyme inhibitors and nonsteroidal anti-inflammatory drugs were the drugs most reported by doctors and pharmacists, producing symptoms at the level of the digestive system and the skin. Keywords: Pharmacovigilance, Adverse reactions, Elderly